1-x分之3-x+x的平方-8x+7分之x的平方-2=1+ 7-x分之5-x 解方程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 00:31:12
1-x分之3-x+x的平方-8x+7分之x的平方-2=1+7-x分之5-x解方程1-x分之3-x+x的平方-8x+7分之x的平方-2=1+7-x分之5-x解方程1-x分之3-x+x的平方-8x+7分之
1-x分之3-x+x的平方-8x+7分之x的平方-2=1+ 7-x分之5-x 解方程
1-x分之3-x+x的平方-8x+7分之x的平方-2=1+ 7-x分之5-x 解方程
1-x分之3-x+x的平方-8x+7分之x的平方-2=1+ 7-x分之5-x 解方程
1-x分之3-x+x的平方-8x+7分之x的平方-2=1+ 7-x分之5-x
(x-3)/(x-1)+(x²-2)/[(x-7)(x-1)]=1+(x-5)/(x-7)
平方同乘以(x-1)(x-7)得:
(x-3)(x-7)+x²-2=(x-1)(x-7)+(x-5)(x-1)
x²-10x+21+x²-2=x²-8x+7+x²-6x+5
4x=-7
x=-7/4
1-x分之3-x+x的平方-8x+7分之x的平方-2=1+ 7-x分之5-x
(3-x)/(1-x)+(x²-2)/(x²-8x+7)=1+(5-x)/(x-7)
(x-3)/(x-1)+(x²-2)/(x-1)(x-7)=1+(x-5)/(x-7)
(x-3)(x-7)+x²-2=(x-1)(x-7)+(x-5)(x-1)
x²-10x+21+x²-2=x²-8x+7+x²-6x+5
-10+14x=12-19
4x=-7
x=-7/4
x的平方+x分之7-x的平方-1分之6+x的平方-x分之3=0
x-3分之x-x的平方-3x分之x+6+x分之1
x分之3+x-1分之6=x的平方-x分之7
1-x分之3-x+x的平方-8x+7分之x的平方-2=1+ 7-x分之5-x 解方程
x的平方-9分之2x+3-x分之1+x+3分之x+2
[(x+3分之x+2)-(x+2分之x+1)+(x+5分之x+4)-(x+4分之x+3)]除以[(x平方+8x+15)分之(x平方+7x+13)]
解方程 x的平方+x分之7-x-x的平方分之3=1+x的平方-1分之7-x的平方
x平方+x分之7 + 1-x平方分之6=x-x平方分之1
计算 【(x+1)分之(x-1)-(x+2)分之(x+1)】/(x的平方+4x+4)分之(x+3)
x-2分之x-(x-2)(x-3)分之1-x的平方=x-3分之2x
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
(x的平方+x分之7)+(x的平方-x分之1)=x的平方-1分之6 (2x-2分之5x+1)+2分之1=3x-3分之4x+10(x+2分之x-1)-(x的平方-4分之x-1)=1(-2-x分之3)在线等
解方程:(1)x的平方+x-2分之3=x-1分之x - x+2分之x解方程:(1)x的平方+x-2分之3=x-1分之x - x+2分之x (2)x的平方-x-6分之5 - x的平方-4分之6 =x的平方-5x+6分之4 (3)x+5分之一 + x+8分之一 = x+6分之
解方程:x平方+x分之7+x平方-x分之3=x平方-1分之6
1-x分之3-x-7-x分之5-x=1-x平方-8x+7分之x平方-2解方程---分式方程
(x分之2x-3 -1)/x分之x的平方-9,其中x=2